2D Covalent‐Organic Framework Electrodes for Supercapacitors and Rechargeable Metal‐Ion Batteries. Issue 4 (5th May 2021) - Kandambeth, Sharath; Kale, Vinayak S.; Shekhah, Osama; Alshareef, Husam N.; Eddaoudi, Mohamed
Abstract: Covalent‐organic frameworks (COFs) represent a new frontier of crystalline porous organic materials with framework structures in 2D or 3D domains, which make them promising for many applications. Herein, the fundamental structural design aspects of 2D‐COFs are reviewed, which position them as suitable electrodes for electrochemical energy storage. The ordered π–π stacked arrangement of the organic building blocks in juxtaposed layers provides a pathway for efficient electronic charge transport; the 2D structure provides a pathway for enhanced ionic diffusion, which enhances ionic transport. Importantly, the tunable pore size enables 2D‐COFs to accommodate mobile ions with different sizes and charges, positioning them as prospect materials for various types of batteries. Distinctively, the ability to functionalize their pore system with a periodic array of redox active species, enriching their potential redox chemistry, provides a pathway to control the redox and capacitive contributions to the charge storage mechanism. The strong covalently linked framework backbone of COFs is an additional merit for achieving long cycle life, and stability against the "leaching out" problem of active molecules in strong electrolytes as observed in other organic materials applied in energy storage devices. Abstract : 2D covalent‐organic frameworks (2D‐COFs) have emerged as promising electrode materials for energy storage applications. The predesignable structure and tailored porosity of 2D‐COFs allow precise integration of redox‐functionalities for energy storage applications. This review features the categorization of various functional linkages deployed for the construction of 2D‐COFs and their key merits as electrode materials for supercapacitors and rechargeable metal‐ion battery applications.